Personality of international celebrity effectiveness towards Celcom Axiata advertisement / Nur Zaratul Afni Mat Lazim and Zati Izni Shapuan - Mat Lazim, Nur Zaratul Afni; Shapuan, Zati Izni (Faculty of Business and Management, 2014)
The use of international celebrity as endorsers has become a popular marketing strategy because it is believed their reputation can positively impact brand. For this study, researcher aim to explore personality of international celebrity effectiveness in Celcom Axiata advertisement. Previous studies found that the effectiveness of the celebrity endorsement depends on three constructs of the source including expertise, attractiveness and trustworthiness (Ng, Chan, & K.Luk, 2013). These three features were studied to gain better understanding the personality of international celebrity effectiveness in produce a strong positive impression. The research questions are 1) which of the personality of international celebrity would be effective in Celcom product advertisement? 2) which elements among the personality of the international celebrities would be effective in Celcom product advertisement? 3) What is the relationship between these personalities and international celebrity effectiveness in product advertisement? The population of this study is Celcom’s subscribers and 150 data had been collected.